Theta Frequency is Associated to Morpho-Strcutural and Perfusional Modifications in Subjects with Mild Cognitive Impairment - Moretti, D.V.; Paternicò, D.; Prestia, A.; Binetti, G.; Zanetti, O.; Frisoni, G.B. (Journal of Psychology and Psychotherapy Research, 2014)
Background: In an attempt to find non-invasive biomarkers, researchers have investigated the feasibility of neuroimaging tools, such as MR, SPECT as well as neurophysiological measurements using EEG. The increase of theta frequency has been associated with mild cognitive impairment (MCI) and related to both grey matter (GM) changes of thalamus and basal ganglia and SPECT modifications. Objective: To study the association of prognostic theta frequency with specific GM and perfusional changes of thalamus and basal ganglia to detect biomarkers early predictive of mild cognitive impairment. Methods: 74 adult subjects with mild cognitive impairment underwent EEG recording and high resolution 3D magnetic resonance imaging (MRI). Moreover, 27 adult subjects with mild cognitive impairment underwent also perfusion single-photon emission computed tomography (SPECT) evaluation. The theta/gamma ratio was computed for each subject. Three groups were obtained according to increasing tertiles values of theta/gamma ratio. Grey matter density differences between groups were investigated using a Voxel Based Morphometry technique. Results: Subjects with higher theta/gamma ratio and increase of theta frequency showed minor atrophy in putamina nuclei bilaterally and a lower hippocampal perfusion in subjects with mild cognitive impairment. Conclusion: The integrated analysis of EEG and morpho-functional markers could be useful in the comprehension of anatomo-physiological underpinning of the MCI entity.